Wasathiyah (Islamic Moderation) and Islamophobia Mitigation: A Comparative Study in Contemporary Islamic Legal Thought in Indonesia - Thohir, Ajid; Ridwan, Ahmad Hasan; Fatahillah, Ikhwan Aulia; Ezzerouali, Souad; Safrudin, Irfan (Universitas Islam Negeri Alauddin Makassar, 2026)
The contemporary escalation of global Islamophobia poses significant challenges not only to social cohesion but also to the legitimacy of Islamic law within modern constitutional frameworks, where it is often perceived as incompatible with universal human rights norms. Despite the expanding discourse on religious moderation, limited attention has been given to evaluating the effectiveness of Indonesia’s Islam Wasathiyah legal framework from a comparative Islamic legal perspective. This study aims to examine the institutionalization of wasathiyah principles within Indonesian Islamic governance and to assess their potential in addressing Islamophobic narratives. Employing a normative juridical approach with a comparative legal framework, this research draws on primary sources including fatwas, state regulations, and policy documents, supported by relevant scholarly literature, and analyzes them through a maqāṣid al-sharī‘ah-based approach combined with doctrinal legal analysis. The findings indicate that the institutionalization of Islam Wasathiyah—through authoritative fatwa mechanisms and state-supported policies—has contributed to the development of a relatively adaptive and inclusive juridical-sociological framework; compared to more rigid approaches in several Muslim jurisdictions, the Indonesian model demonstrates a greater capacity to accommodate pluralism and respond to contemporary socio-legal challenges, including Islamophobic discourse. This study contributes to contemporary Islamic legal scholarship by offering a contextualized model of religious governance grounded in maqāṣid al-sharī‘ah, which has the potential to strengthen the position of Islamic law within pluralistic societies while providing a constructive framework for mitigating Islamophobia.